Knowledge and Technology Transfer in Medicine and the Health Sciences: An Introduction - Baca Baldomero, Enrique (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
An analysis of the concept of the transfer of knowledge, in general, and, in particular, its application to the health system. Three aspects of the transfer of knowledge are analysed: concepts and data; technology and values; and the directions it takes, that is to say centripetally from the cordon of sciences outside the health system itself (or any specific field of knowledge) and centrifugally from this out to the general public. This exchange of knowledge (transfer, transmission, dissemination; all three variants are analysed in the piece) includes, as well as the knowledge itself, values that modify both the nucleus generating knowledge and its recipients. It is necessary, in our so-called communication or information society, to find out and quantify how transfers of knowledge (concepts, data and technology) influence the appearance of values arising from these transfers.